Properties of ammonia‐oxidising bacteria and archaea in a hypereutrophic urban river network. (2nd November 2021) - Cai, Xianlei; Yao, Ling; Wang, Siyu; Hu, Yuanyuan; Dahlgren, Randy A.; Wang, Zhenfeng; Deng, Huanhuan; Liu, Lizhen
Abstract: Ammonia oxidation by ammonia‐oxidising archaea (AOA) and bacteria (AOB) is the first and rate‐limiting step of nitrification. By providing substrate to the nitrogen–removing denitrification processes, nitrification is an important process for attenuation of allochthonous nitrogen loads in urban rivers, thereby mitigating eutrophication of downstream ecosystems. However, the relative importance of AOA and AOB communities in ammonia oxidation, the distribution and varied patterns of these groups and the underlying mechanisms have received limited study in hypereutrophic urban river networks. To investigate spatial and temporal patterns of particle‐attached and free‐living ammonia‐oxidising microbial communities, we conducted a 2‐year study of four different water quality/habitat conditions within a hypereutrophic urban river network of eastern China. The structure and dynamics of ammonia‐oxidising microbial communities were determined by high‐throughput sequencing based on the AOA and AOB amoA gene. We found significant spatial and temporal heterogeneity of ammonia‐oxidising microbial communities, but no significant differences between particle‐attached and free‐living fractions. Analysis revealed that changes in the diversity and composition of ammonia‐oxidising microbial communities were mainly related to substrate availability (e.g., ammonia, nitrite, dissolved oxygen). AOB communities were more complex and had a higher species richness and diversity compared with AOA communities. Our findings indicate that high anthropogenic nitrogen loadings appear to promote higher ammonia‐oxidising microbial richness and diversity, and AOB are more adaptable to the hypereutrophic conditions, thereby playing a more important role than AOA in nitrogen transformations in hypereutrophic urban river networks. This study highlights the importance of ammonia‐oxidising microorganisms in nutrient‐rich river systems and provides valuable insights into ammonia transport and transformations in urban river networks.